2018
DOI: 10.1111/nep.13183
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pulmonary artery systolic pressure and right ventricular function in patients with end‐stage renal disease on maintenance dialysis

Abstract: In patients with end-stage renal disease, PASP increases over time. Changes are moderately predictable. Higher PASP predicted development of right ventricular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 34 publications
1
21
1
2
Order By: Relevance
“…Regarding the risk factors associated with survival, age, diabetes [ 13 , 19 – 21 ], serum albumin [ 19 ], BMI [ 13 ], and cardiovascular disease [ 21 , 22 ] were not consistent with our results. Importantly, age is one of the major factors affecting survival in dialysis patients, which is consistent with our findings.…”
Section: Discussioncontrasting
confidence: 76%
“…Regarding the risk factors associated with survival, age, diabetes [ 13 , 19 – 21 ], serum albumin [ 19 ], BMI [ 13 ], and cardiovascular disease [ 21 , 22 ] were not consistent with our results. Importantly, age is one of the major factors affecting survival in dialysis patients, which is consistent with our findings.…”
Section: Discussioncontrasting
confidence: 76%
“…Hypercholesterolemia was associated with increased mortality in HD patients without myocardial infarction/ cardiovascular disease 18 . Higher pulmonary artery systolic pressure predicted development of right ventricular dysfunction, which portends a poor prognosis 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Right ventricular dysfunction and PH defined as a mean pulmonary arterial pressure ≥ 25 mmHg are common complications in patients on conventional hemodialysis and peritoneal dialysis . Yet, studies of right ventricular function and PH in patients undergoing dialysis are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Right ventricular dysfunction and PH defined as a mean pulmonary arterial pressure ≥ 25 mmHg are common complications in patients on conventional hemodialysis and peritoneal dialysis. 1,2 Yet, studies of right ventricular function and PH in patients undergoing dialysis are scarce. Two studies reported on reduction of left and right ventricular end systolic volumes and reduction of right ventricular end-systolic volume index after hemodialysis was intensified.…”
Section: Discussionmentioning
confidence: 99%